Reinforcing Concrete Slabs Using Cellulose Fiber - CHEN Xiaopan; CHANG Shiju; JIA Peng; YU Chuanyong; WANG Likui; ZHAO Jie; TAN Jianjun (Guan'gai paishui xuebao, 2023)
【Objective】 Cellulose fiber is a material increasingly used to reinforce concrete and this paper investigates its improvement of concrete slabs against cracking. 【Method】 Concrete slabs made by cement mixed with fly ash, cement mixed with fly ash and MgO, were compared with slabs made by cement-fly ash reinforced by cellulose fiber. For each slab, we measured its strength, deformation property, resistance against macro-cracks and emergence of micro-crack. 【Result】 Concrete slab reinforced by cellulose fibers are mechanically best, and its splitting tensile strength and ultimate tensile strength are both higher than other slabs. The cellulose fibers not only delays the initiation of cracks but also reduces cracking density (numbers of cracks per unit area). Ninety days after the slab is casted, SEM analysis shows that the structure of the reinforced slabs is relatively compact and a large number of short-rod clusters are formed inside it. Energy spectrum analysis shows that the cellulose fiber reduces the proportion of calcium while increasing the proportion of silicon and aluminum in the slabs. Fly ash hydration consumes a certain amount of calcium, thereby reducing the calcium-silicon ratio and increasing the strength of the slabs. 【Conclusion】 Comparison shows that reinforcing concrete slabs by cellulose fiber can significantly improve their resistance against cracking and tensile strength.